2020
DOI: 10.1186/s12890-020-01185-9
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of patients with acute exacerbation of combined pulmonary fibrosis and emphysema: a retrospective single-centre study

Abstract: Background: Previous analyses of combined pulmonary fibrosis and emphysema (CPFE) cohorts have provided conflicting data on the survival of patients with CPFE. Therefore, the aim of this study was to investigate the clinical prognosis of acute exacerbations (AE) of CPFE. Methods: We retrospectively reviewed the medical records of patients who had been treated at the Shinshu University Hospital (Matsumoto, Japan) between 2003 and 2017. We identified 21 patients with AE of CPFE and 41 patients with AE of idiopat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
10
0
2
Order By: Relevance
“…Previous studies have reported that the prognosis of acute exacerbation is favorable, and that acute exacerbation is less frequent in patients with CPFE than in patients with IPF. However, it may have lethal consequences and careful monitoring is needed [ 73 , 74 ]. Zantah et al [ 74 ] stratified exacerbation events in patients with CPFE into acute exacerbation of COPD (AE-COPD) and AE-IPF.…”
Section: Prognosismentioning
confidence: 99%
“…Previous studies have reported that the prognosis of acute exacerbation is favorable, and that acute exacerbation is less frequent in patients with CPFE than in patients with IPF. However, it may have lethal consequences and careful monitoring is needed [ 73 , 74 ]. Zantah et al [ 74 ] stratified exacerbation events in patients with CPFE into acute exacerbation of COPD (AE-COPD) and AE-IPF.…”
Section: Prognosismentioning
confidence: 99%
“…Previous studies have reported that the prognosis of acute exacerbation is favorable, and that acute exacerbation is less frequent in patients with CPFE than in patients with IPF. However, it may have lethal consequences and careful monitoring is needed 73,74 . Zantah et al stratified exacerbation events in patients with CPFE into acute exacerbation of COPD (AE-COPD) and acute exacerbation of IPF (AE-IPF) 74 .…”
Section: Prognosis Of Cpfementioning
confidence: 99%
“…The exact annual risk of AE-CPFE is unknown but appears to be less frequent than AE-IPF. A retrospective study that compared the clinical outcome of patients with AE-CPFE with that of patients with AE-IPF showed a significantly better prognosis and a higher survival rate in AE-CPFE [117]. The treatment and management of patients with AE-CPFE reflect the type of underlying exacerbation (COPD-type or IPF-type).…”
Section: Exacerbations Of Cpfementioning
confidence: 99%